THE USE OF E-SABAK IN MATHEMATICS LEARNING TO OPTIMIZE HIGHER-ORDER THINKING SKILLS - Fajri, Muhammad (UIN Sunan Kalijaga Yogyakarta, 2020)
This study aims to describe the using of e-sabak in optimizing the higher-order thinking skills in mathematics learning. The obtaining data on the description of mathematics learning through the use of e-sabak in optimizing higher-order thinking skills, this research applied a qualitative approach with a descriptive method. The research instrument utilized observation and documentation guidelines to photograph mathematics learning in optimizing the ability to think at a higher level through the use of e-sabak in fourth-grade students at SDN Pondok Petir 01, Depok City. The results showed: (1) students were happy with new experiences in the use of e-sabak; (2) the use of e-sabak devices can optimize the ability of students to analyze and evaluate phenomena through observation by capturing them using e-sabak; (3) teacher provided the ways of communicating observations in front of the class to students; (4) the ability of students to create a problem-solving context still needs to be optimized through the praxis of learning in the classroom context. This study concluded that the e-sabak device helps the implementation of mathematics teaching to maximize the ability of high-level thinking students in fourth grade SDN Pondok Petir 01, Depok City.